The effect of curing time and curing method on microleakge of conservative adhesive resin restorations: an in vitro study - Alireza Heidari; Mehdi Shahrabi; Sara Ghadimi; Shahram Mosharafian; Zohreh Rafiee (Tehran University of Medical Sciences, 2012)
Background and Aims: Using the conservative adhesive resin restoration (CAR) in uncooperative children lead to numerous problems because of being time consuming. The purpose of this study was to compare the microleakage of conservative adhesive resin restoration under separate curing and co-curing.Materials and Methods: In this experimental study, 120 intact premolar teeth were collected and 120 vertical grooves were prepared on them. Then the teeth were divided into four groups: group 1, separated curing of bonding agent, flowable composite and sealant; group 2, co-curing of all materials for 60 seconds; group 3,co-curing of all materials for 40 seconds and group 4, co-curing of all materials for 20 seconds. Then the specimens were thermocycled and immersed in basic fuchsin solution. The teeth were sectioned horizontally and dye penetration was evaluated with stereomicroscope. Date were analyzed using one-way ANOVA and Scheffe test.Results: Mean value of dye penetration in groups 1, 2, 3, and 4 was 1.53±0.6, 2.06±0.6, 2.5±0.7 and 3.53±0.6, respectively. There was a statistically significant difference between group 1 and the other groups (P=0.0001).Conclusion: Considering the problems caused by microleakage in conservative resin adhesive restorations, co-curing method should not be used. In the case of using co-curing method, 60 second curing time is suggested for sufficient polymerization.